THE DESIGN OF NIAS TRADITIONAL DANCE ENCYCLOPEDIA MODEL BASED ON DIGITAL TECHNOLOGY - Tuti Rahayu; Wiflihani (International Journal of Performing Arts (IJPA), 2022)
The purpose of this study is creating a product of a digital-based encyclopedia on the concept of Nias ethnicity dance traditions in North Sumatra. This research led to a reference book product in the form of an e-book. This type of research method used is the Research and Development (R&D) method. The location of this study was conducted in the cities of Medan and Nias. Data collection techniques through observation, in-depth interviews, and documentation. Data is analyzed using a qualitative paradigm using project-based research, which is obtained through data reduction, data presentation and drawing conclusions. The results of the design of this Nias tradition dance encyclopedia book can be used for reference for students and the public about Nias regional dance traditions.